2021
DOI: 10.3390/cancers13225671
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets and Emerging Therapies for Advanced Gallbladder Cancer

Abstract: Biliary tract cancers (BTCs), for their low incidence, have been often considered together. Gallbladder cancer (GBC) is the most common biliary tract malignancy, characterized by late diagnosis and poor prognosis, and although it is considered a rare tumor in western countries, other areas of the world show considerable incidence rates. In 2010, results from the large phase III ABC-02 clinical trial on GBC identified the gemcitabine and cisplatin combination as the most effective first-line regimen for both GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 114 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…As a result of the relative rarity, difficulties in obtaining preneoplastic cells and benign background epithelial cells for study, and other reasons, there is little scientific knowledge on gallbladder precursor lesions compared to lesions in other organs [ 70 , 71 ]. We hope recent new technologies will provide precision data regarding precursor neoplastic lesions of the gallbladder in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the relative rarity, difficulties in obtaining preneoplastic cells and benign background epithelial cells for study, and other reasons, there is little scientific knowledge on gallbladder precursor lesions compared to lesions in other organs [ 70 , 71 ]. We hope recent new technologies will provide precision data regarding precursor neoplastic lesions of the gallbladder in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…54 Recently, the FUGA-BT (JCOG1113) phase III randomized clinical trial in 354 Japanese patients with advanced/recurrent biliary tract cancer (including 137 patients with GBC; 38.7% of the population) showed that a combination of gemcitabine and an oral fluoropyrimidine (S1) was noninferior to the gemcitabine/cisplatin combination (median overall survival 15.1 vs. 13.4 months, respectively; HR: 0.945; 90% CI: 0.78-1.15; P = 0.046). 74,75 Similarly, another Japanese phase III trial (KHBO1401-MITSUBA) showed a slight benefit of the gemcitabine/cisplatin/S-1 combination over gemcitabine/ cisplatin) in advanced biliary tract cancer, including GBC. 76 Lastly, adjuvant chemotherapy before recurrence has been shown to improve the overall survival in patients with recurrent GBC after curative intent surgery (HR = 0.56, P = 0.027).…”
Section: Discussionmentioning
confidence: 99%
“…In patients diagnosed with resectable GBC with curative intent, adjuvant capecitabine is indicated based on the BILCAP trial that showed an improvement of overall survival by 17 months in patients with resectable biliary tract malignancies, including a 17.7% of the population diagnosed with GBC 54. Recently, the FUGA-BT (JCOG1113) phase III randomized clinical trial in 354 Japanese patients with advanced/recurrent biliary tract cancer (including 137 patients with GBC; 38.7% of the population) showed that a combination of gemcitabine and an oral fluoropyrimidine (S1) was noninferior to the gemcitabine/cisplatin combination (median overall survival 15.1 vs. 13.4 months, respectively; HR: 0.945; 90% CI: 0.78-1.15; P =0.046) 74,75. Similarly, another Japanese phase III trial (KHBO1401-MITSUBA) showed a slight benefit of the gemcitabine/cisplatin/S-1 combination over gemcitabine/cisplatin) in advanced biliary tract cancer, including GBC 76.…”
Section: Discussionmentioning
confidence: 99%
“…GBC is an extremely aggressive cancer with 5-year survival rate no more than 5%, especially for those advanced-stage patients. There still no curable treatment methods for advanced GBC patients [ 23 , 24 ]. It is critical to clarify the underlying mechanisms of GBC progression.…”
Section: Discussionmentioning
confidence: 99%